BIOCHEMICAL ANALYSIS OF BITLIS-HIZAN (TURKEY) REGION'S HONEY - Ozsahin, A. D.; Demirkol, Y.; Kirmizikaya, G.; Kirecci, O. A. (Aloki Applied Ecological Research and Forensic Inst Ltd, 2024)
In this study, biochemical analyses of honey produced in Hizan district of Bitlis province which is one of the important honey centers of Turkey, were performed. In the research, 7 honey samples collected from villagers dealing with beekeeping in different regions of Hizan were studied. Hydroxymethylfurfural (HMF), antioxidant activities, sugar, flavonoid and total phenolic levels were measured with the HPLC device. As a result, the flavonoid, sugar and total phenolic levels of 1, 4, 5 and 7 honeys were similar to the properties of natural honeys. The HMF values of all honey samples were found to be in accordance with the value determined in the Turkish Food Codex Honey Communiqu & eacute;. It was determined that the honeys used in our study have scavenging properties on DPPH and ABTS radicals. In addition, the maltose value of the 3 and 5 honey samples was found to be slightly higher than that of the other honey samples. Since maltose is formed as a result of the hydrolysis of starch, it cannot be found naturally in plant juices. Honey samples with high maltose content are considered to be produced under unnatural conditions. The antioxidant and chemical properties of Bitlis-Hizan honey make them high value-added quality products. As a result, it was seen that the results comply with EU standards and the Turkish Food Codex Honey Communiqu & eacute;.
Keywords: ABTS; Bitlis (Hizan) honey; DPPH; HMF; phenolic compounds